MOLECULAR IDENTIFICATION AND COMPARATIVE ANTIMYCOPLASMAL ACTIVITY OF THREE INDIGENOUS MEDICINAL PLANTS AGAINST MYCOPLASMA PUTREFACIENS ISOLATED FROM SHEEP - M. K. Shah; U. Sadique; S. Ahmad; S. Qureshi; S. U. Rahman; Z. U. Hassan; M. A. Khan; T. Ali; F. Anwar; H. Khan; H. Khan (Journal of Animal and Plant Sciences, 2017)
Medicinal plants are used for the treatment of human and animal diseases from the ancient time. Screening of medicinal plants for bioactive compound leads to development of new and cheap antimicrobial agents. The present study was carried out to investigate the molecular identification of Mycoplasma putrefaciens and to evaluate the antimycoplasmal activity of methanolic extract of three medicinal plants, i.e., Artemisia herba-alba, Calotropis procera and Azadirachta indica against local isolates of M. putrefaciens obtained from sheep of different regions of Khyber Pakhtunkhwa, Pakistan. The result showed that significantly (P ˂ 0.001) higher number of isolates were obtained from southern (n=43; 14.33%) followed by central zone (n=26; 8.66%).  A total of 60 PCR confirmed M. putrefaciens isolates (20 from each zone) were subjected to antimycoplasmal activity of plant extracts. The plant extracts were tested against the isolates using agar well diffusion assay by determining the zone of inhibition and broth microdilution method for minimum inhibitory concentrations (MICs). The results showed that the methanolic extract of Artemisia herba-alba exhibited prominent antimycoplasmal activity at 30 mg by producing maximum zone of inhibition (15.4±0.52 mm) against all the tested isolates followed by Calotropis procera and Azadirachta indica with inhibition zones of 14±0.58 and 11±0.7 mm, respectively. Whereas, the MICs values were 0.03±0.001, 0.3±0.04 and 3.0±0.2 mg/mL for A. herba-alba, C. procera and A. indica, respectively. The results of this study suggest that methanolic extract of all the three indigenous plants exhibited strong antimycoplasmal activity against M. putrefaciens, which might be used successfully for the treatment of mycoplasmosis.
Keywords: Mycoplasma; sheep; medicinal plants; methanolic extracts; agar well diffusion; MICs